Relationships between osteoarthritic changes (osteophytes, porosity, eburnation) based on historical skeletal material - Anna Myszka; Janusz Piontek; Jacek Tomczyk; Aleksandra Lisowska-Gaczorek; Marta Zalewska (Taylor & Francis Group, 2020)
Background: Three main diagnostic types of osteoarthritic changes are distinguished in clinical and anthropological literature: osteophytes, porosity, and eburnation. The nature of the relationship between these changes and how lesions progress over time is still unclear. Aim: The aim of the present study is the analysis of the relationships between osteophytes, porosity, and eburnation based on skeletal material. Subjects and methods: The analysis employed the skeletal collection from Cedynia (199 individuals) from tenth to fourteenth-century Poland. Marginal osteophytes (OP), porosity (POR), and eburnation (EB) were examined on a shoulder, elbow, wrist, hip, knee, and ankle. Results: Osteophytes and porosity occurred independently of each other. Combinations of osteophytes and porosity (OP + POR) and osteophytes, porosity, and eburnation (OP + POR + EB) were rarely observed. Combinations of osteophytes and eburnation (OP + EB) or porosity and eburnation (POR + EB) were not found. There was a significant correlation between osteophytes and porosity in the scapula, proximal end of the ulna and proximal end of the femur. Osteophytes and eburnation were correlated at the distal end of the ulna. Porosity and eburnation were correlated at the distal end of the radius and distal end of the ulna. When all joints were considered together, all the types of osteoarthritic changes were correlated. However, the relationship between osteophytes and eburnation and between porosity and eburnation was only slightly significant. Osteophytes preceded porosity, but there were a few cases where more developed porosity accompanied less developed osteophytes. Conclusions: The findings indicate that correlations between osteoarthritic changes are weak, albeit statistically significant and further studies of the relationship between changes are necessary.